The character of Electra in the plays of Aeschylus, Sophocles and Euripides (Philologia, 2021)
Greek myths have always been a rich source of inspiration for many playwrights and one of the most famous myths is Agamemnon’s murder and vengeance on the mother who committed it. Among many characters that appear in the myth, Electra deserves meticulous attention and inspired even the Ancient Greek dramatists Aeschylus, Sophocles and Euripides, who approached the story in three different ways. Aeschylus regarded the matricide as a necessity and Electra in his play is both emotional and indecisive. Sophocles saw Electra as a tortured heroine who does not have limits. Euripides, the last of these playwrights to deal with the myth, provides a lot of criticism for the traditional myth and in his play Electra is not only anti-heroine but also pathological character. After Euripides, the importance of tragedy fades away in the Ancient Greece and the plays were not written anymore in the manner of the greatest playwrights.
Keywords: myth; play; murder; revenge; matricide; tragedy; gods